Pengkajian Agama Secara Historis - Tarigan, Mardinal; Aprila, Gusti; Pratama, Riswanda (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
As we know that history cannot be separated from a series of events that have been limited by space and time in which these events were formed and occurred. Many people say that history is something static that cannot possibly be "recycled" based on the context of its era. Along with the development of human knowledge, with the potential for great curiosity, it has influenced people's perspectives on history, who previously considered that history was only a static event, rigid and did not even have any contribution to the advancement of scientific studies, but this view automatically disappeared in the womb of the struggle for study. Islam, where history is always dynamic, along with the "pulse flow" of the development of human civilization. This paper uses a heuristic method using critical analysis sourced from primary books.With the heuristic method as an analytical tool to dissect the peculiarities of the past, it can be interpreted because it is seen as having a unique influence on the present and the future. It is in this context that efforts are made to link the relevance of Islamic education as a field of life that is experiencing challenges. These challenges are examined from various perspectives, including studying Islamic education from a historical perspective. It is at this point that the dynamics of Islamic education can be meaningful for the development of science. Keywords: Study, Historical, Islamic Education